Storyboard '08 : a new approach to a local film festival. - Ong, Chor Hao. (2009)
This project studied the impact of using film festivals as a tool to develop and expand the local film community. After examining the roles and influences of film festivals on the film industry, and supplemented by in-depth studies of prevailing attitudes towards the local film scene, the team concluded that a new model that can integrate both filmmakers and the public’s demands into its programming was feasible and necessary. Storyboard ’08 was a youth-oriented film festival designed to encourage the general public’s participation and to provide platforms for young filmmakers for showcase and growth. Despite being an inaugural campaign, its success assured the team of the future viability of Storyboard.